Evaluating the Impact of an Innovative Educational Program for Skin Care Champions Using the Pieper-Zulkowski Pressure Ulcer Knowledge Test. (May 2020) - Delmore, Barbara; Smith, Daniel J.; Savage, Elizabeth; Ayello, Elizabeth A.
ABSTRACT: OBJECTIVE: To assess pressure injury knowledge of Skin Care Council nursing members using the Pieper-Zulkowski Pressure Ulcer Knowledge Test (PZ-PUKT), to design an educational intervention informed by the results of the baseline assessment, and to evaluate the effect of the intervention. METHODS: This was a single-group pretest-posttest project conducted in an urban, academic, tertiary medical center from January to August 2017. Participants were measured on the pretest, received the intervention, and then were reevaluated on the posttest 3 months later. Pretest results informed the design of the intervention, which was a 1-day interactive, targeted educational program referred to as the "Skin Care Council Boot Camp." Paired-samples t tests were conducted to examine differences between pretest and posttest scores on the PZ-PUKT overall and in each test section. RESULTS: Seventy-seven participants enrolled in the project and completed the pretest. Of those, 58 (75.3%) were retained through the intervention and the posttest evaluation. Participants had a mean pretest score of 78.9 and a mean posttest score of 85.3. There were significant mean differences among pretest and posttest PZ-PUKT scores: 6.4 ( t = 9.419, P < .001) overall; 4.6 ( t = 5.356, P < .001) in the Prevention/Risk category; 4.1 ( t = 3.668, P < .001) in the Staging category; and 10.5 ( t = 7.938, P < .001) in the Wound Description category. CONCLUSIONS: By testing pressure injury knowledge before developing a program, investigators created a tailored, education program that addressed knowledge gaps. Posttest results provided insight into the program's success and opportunities for future improvement.